Health workers' views on quality of prevention of mother-to-child transmission and postnatal care for HIV-infected women and their children - Hardon Anita; Pham Yen; Oosterhoff Pauline; Nguyen Thu Anh; Wright Pamela (BMC, 2009)
Abstract Background Prevention of mother-to-child transmission has been considered as not a simple intervention but a comprehensive set of interventions requiring capable health workers. Viet Nam's extensive health care system reaches the village level, but still HIV-infected mothers and children have received inadequate health care services for prevention of mother-to-child transmission. We report here the health workers' perceptions on factors that lead to their failure to give good quality prevention of mother-to-child transmission services. Methods Semistructured interviews with 53 health workers and unstructured observations in nine health facilities in Hanoi were conducted. Selection of respondents was based on their function, position and experience in the development or implementation of prevention of mother-to-child transmission policies/programmes. Results Factors that lead to health workers' failure to give good quality services for prevention of mother-to-child transmission include their own fear of HIV infection; lack of knowledge on HIV and counselling skills; or high workloads and lack of staff; unavailability of HIV testing at commune level; shortage of antiretroviral drugs; and lack of operational guidelines. A negative attitude during counselling and provision of care, treating in a separate area and avoidance of providing service at all were seen by health workers as the result of fear of being infected, as well as distrust towards almost all HIV-infected patients because of the prevailing association with antisocial behaviours. Additionally, the fragmentation of the health care system into specialized vertical pillars, including a vertical programme for HIV/AIDS, is a major obstacle to providing a continuum of care. Conclusion Many hospital staff were not being able to provide good care or were even unwilling to provide appropriate care for HIV-positive pregnant women The study suggests that the quality of prevention of mother-to-child transmission service could be enhanced by improving communication and other skills of health workers, providing them with greater support and enhancing their motivation. Reduction of workload would also be important. Development of a practical strategy is needed to strengthen and adapt the referral system to meet the needs of patients.